The Effects of Economic Activities Diversification on Development: the Perspective of Serbia - JEDNAK, Sandra; Makajić-Nikolić, Dragana; Kragulj, Dragana; Vujošević, Mirko (Industrija, 2016)
Each economy specializes in certain economic activities depending on the development level and availability of resources. During their development, countries undergo sectoral transformation. In order to achieve a higher level of economic development, it is necessary for a country to diversify its economic activities and determine which economic activities should be invested in. The aim of this paper is to analyse the effects of economic structure and diversification activities on the development of Serbia for the period 2007-2012. Optimization model has been used to present diversification of activities. Furthermore, the efficiency frontier is used to show returns, risks and correlation among activities. The results show that the economic activities – Mining and quarrying, Public administration and defence, Compulsory social security, Other service activities, Financial and insurance activities, Arts, entertainment and recreation should be drivers of economic growth, because they provide a balance between growth and security regarding GVA in economic activities.